A scientific theology ; v. 3 - McGrath, Alister Edgar, 1953- (London, UK T and T Clark, 2003)
Contents : v. 3 : Theory. Includes bibliograhical references and index.
Keywords: Scientific theory -- religious aspects -- Christianity